Turning Plastic Waste Immiscibility into an Advantage: Efficiency Improvement of PVDF‐Based Energy Harvesters Using Post‐Consumer Thermoplastics - Petr Slobodian; Berenika Hausnerova; Pavel Riha; Vladimir Pata; Robert Olejnik; Jiri Matyas (Advanced Materials Interfaces)
Abstract The immiscibility of plastic waste, which is often a limiting factor in traditional recycling processes, is considered in this study as a key feature for functional material design. Polyvinylidene fluoride (PVDF), renowned for its exceptional triboelectric and piezoelectric properties, is combined with post‐consumer thermoplastic waste from the packaging industry to create a novel, sustainable energy‐harvesting solution. Immiscible compounds of wasted high‐density polyethylene, polypropylene, polystyrene, and polyethylene terephthalate form physical mixtures of domains of individual polymers within the melt, which enhance mechano‐electric conversion when paired with PVDF to achieve a remarkable output voltage of 800 V, with short‐circuit current and charge densities reaching 260 µAcm⁻2 and 710 nCm⁻2, respectively, surpassing traditional PVDF‐nanoparticle composites. This method not only reduces reliance on costly nanomaterials but also demonstrates the potential of repurposed plastic waste for energy applications. The design of the sensors is examined to distinguish the contribution of piezo‐ and tribo‐electrifications. Examples of low‐cost sustainable sensors constructed from PVDF and thermoplastic waste films demonstrate efficient energy conversion and sensitivity to mechanical stimuli and highlight the potential of repurposing immiscible plastic waste not only as a solution to pollution but also as a contributor to green energy technologies.